SHORT EPISODES OF CRUST GENERATION DURING PROTRACTED ACCRETIONARY PROCESSES: EVIDENCE FROM CENTRAL ASIAN OROGENIC BELT, NW CHINA - Gong-Jian Tang; Sun-Lin Chung; Chris J. Hawkesworth; P. A. Cawood; Qiang Wang; Derek A. Wyman; Yi-Gang Xu; Zhen-Hua Zhao (Геодинамика и тектонофизика, 2017)
continental crust but the spatial and temporal distribution of crust generation within individual orogens remains poorly constrained. Paleozoic (~540–270 Ma) granitic rocks from the Alati, Junggar and Chinese Tianshan segments of the Central Asian Orogenic Belt (CAOB) have markedly bimodal age frequency distributions with peaks of ages at ~400 Ma and 280 Ma for the Altai segment, and ~430 Ma and 300 Ma for the Junggar and Chinese Tianshan segments. Most of the magma was generated in short time intervals (~20–40 Ma), and variations in magma volumes and in Nd–Hf isotope ratios are taken to reflect variable rates of new crust generation within a long-lived convergent plate setting.